DEVDase activity is induced in potato leaves during Phytophthora infestans infection. - Fernández, M.B. (2012)
Programmed cell death (PCD) occurs in plants, animals and several branches of unicellular eukaryotes as a part of developmental and/or defense processes. Caspase proteases are universal mediators of animal apoptosis, a type of PCD. In plants, there are not animal caspase homologs; therefore, the characterization of caspase-like activities is of considerable importance to our understanding of PCD in plants. Here we report for the first time the involvement of caspase-3-like activity in the resistance mechanism of potato to Phytophthora infestans infection. We showed that disease development in infected potato leaves is dependent of caspase-3-like activity. Unlike plant DEVDases previously reported, this DEVDase activity was sensitive to the serine protease inhibitor PMSF. As reported for other subtilisin- like proteases with caspase activity, potato DEVDase activity was mainly localized in the apoplast. We demonstrated that in total protein extract DEVDase activity accounts for a 60% of serine prot